HUBUNGAN ASUPAN KARBOHIDRAT, LEMAK, DAN PROTEIN DENGAN STATUS GIZI (Studi Kasus pada Pekerja Wanita Penyadap Getah Karet di Perkebunan Kalijompo Jember) - Nabila Permata Siwi; Indriati Paskarini (Universitas Airlangga, 2018)
Kalijompo Plantation is one of rubber plantations in Jember. One of rubber production is rubber tapping that is done not only by male but also female workers. One of the factors that can affect productivity is nutrition status. Nutrition status is influenced by the adequancy of nutrients, especially carbohydrates, fats, and proteins as energy producers. The purpose of this research was to study the correlation between carbohydrates, fats, and proteins intake with nutrition status in female tap rubber workers of Kalijompo Plantation in Jember. This research was analytical observational research and had a cross sectional design. The population of this research were all female tap rubber workers of Kalijompo Plantation in Jember with the sample consisted of 33 respondents. The variables of this research carbohydrates intake, fats intake, proteins intake, and nutrition status. Data collection included measurement of weight body, measurement of height body, and food recall 1x24 hours.The results showed that there was no correlation between carbohydrates intake with nutrition status (p=0.968), there was no correlation between fats intake with nutrition status (p=0.646), and there was no correlation between proteins intake with nutrition status (p=0.679). The conclusion of this research was the intake of carbohydrates, fats, and proteins are not factors that can affect good or bad nutrition status in female rubber tapping workers of Kalijompo Plantation in Jember.